Differences and correlations between microstructure and macroscopic properties of mesophase cokes derived from the components of high temperature coal tar pitch. (15th February 2022) - Hu, Chaoshuai; Chu, Hongyu; Zhu, Yaming; Xu, Yunliang; Cheng, Junxia; Gao, Lijuan; Lai, Shiquan; Zhao, Xuefei
Highlights: Ultrasonic assisted extraction is an effective method to treat CTP. OTI can be used as a reference index to comprehensively evaluate mesophase cokes. Parameter of ID1 /IG is proposed to evaluate graphite structure size in mesocokes. Macroscopic properties and microstructure can be inferred from each other. Abstract: It has been universally believed that the soluble and insoluble components of coal tar pitch obtained by solvent extraction were good precursors to prepare mesophase cokes. The microstructure and macro properties of mesophase cokes derived from the soluble and insoluble components are varied in general. In order to study the differences and correlations between the microstructure and macro properties of mesophase cokes, 16 kinds of component in two categories have been prepared mesophase cokes as the raw materials. Briefly, Scanning electron microscope (SEM), Polarizing Microscope (PM), Raman spectroscopy, X-Ray Diffraction (XRD), thermogravimetry (TG) and Micro-strength intensity (MSI) have been used to characterize microstructure and macro properties of cokes. In fact, the graphite structure in extract-based cokes is larger and more orderly than that in residue-based cokes. The MSI of residue-based cokes (66 ∼ 81%) is higher than that of extract-based cokes (53 ∼ 60%), while Tmax (615 ∼ 645 ℃ and 680 ∼ 715 ℃) of the two are opposite. In a word, the results indicate that all data of the two categories of cokes go to bipolar distribution. And the results of this work were helpful for understanding and providing direction for the evaluation of cokes used to prepare isotropic and anisotropic graphite.